Perancangan Manajemen Bumdes dalam Meningkatkan Perekonomian Desa di Desa Beji Kecamatan Kedungbanteng Kabupaten Banyumas - Oti Kusumaningsih; Devit Bagus Indranika; Anggara Setya Saputra; Ranjani Ranjani; Suryoto Suryoto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The existence of Law Number 6 of 2014 concerning Villages makes the village a strategic autonomous region. This can be a challenge for the village to take advantage of all the potential that exists, especially in improving the economy of the community. BUMDes is one of the efforts to improve the village economy. BUMDes is considered a business entity that supports the village economy if it is managed properly. But in reality, BUMDes in Indonesia are still far from expectations. The problem that often arises is in the management of BUMDes itself, especially in Beji Village, Kedungbanteng District, Banyumas Regency. The service method used is a focus group discussion (FGD) technique where the method uses qualitative data collection conducted by means of interviews guided by a moderator. The results shown are the response and support for every aspect, namely from the village government, community leaders and the general public. This is the first step and strategy in stimulating the community to achieve the goals of this service. The Beji Village BUMDes management design has begun to be initiated again with more professional and credible management so that the functions and roles of BUMDes can run according to the expectations of all parties. This is indicated by the re-recruitment of BUMDes managers in accordance with the standards. In addition, Beji Village BUMDes management has been systematized and structured, starting from the preparation of BUMDes planning, BUMDes management to BUMDes reporting and accountability forms.